2017
DOI: 10.1259/bjr.20160352
|View full text |Cite
|
Sign up to set email alerts
|

Aetiologies of internal carotid artery pseudo-occlusions in acute stroke patients: what neurointerventionalists can expect

Abstract: In cases of acute stroke, differentiation between an occluded and a patent internal carotid artery (ICA) is crucial for diagnosis and management. Although CT angiography (CTA) can be highly accurate in defining high-grade stenosis and ICA occlusions, misleading ICA occlusion patterns are not rare in patients with acute stroke. We investigated the underlying causes of ICA pseudo-occlusions with CTA with respect to digital subtraction angiography. 11 out of 72 patients had pseudo-occlusion on CTA. Of these, ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 10 publications
1
9
0
Order By: Relevance
“…Thus, we ultimately included 71 patients with a mean age 70 ± 14 years; 41 (57.7%) were male. The median NIHSS score on admission was 19 (interquartile range [16][17][18][19][20][21]. Of all patients, 56.3% (n = 40) exhibited cICA-POs combined with distal ICA occlusions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, we ultimately included 71 patients with a mean age 70 ± 14 years; 41 (57.7%) were male. The median NIHSS score on admission was 19 (interquartile range [16][17][18][19][20][21]. Of all patients, 56.3% (n = 40) exhibited cICA-POs combined with distal ICA occlusions.…”
Section: Resultsmentioning
confidence: 99%
“…Patients with cICA-POs often have thrombi extending below the level of the posterior communicating artery, thus occluding that artery. Such patients tend to have larger clots (filling the terminal ICA segment) than those without cICA-POs (who usually exhibit contrast-filling of the posterior communicating artery, triggering adequate, antegrade, Willisian circle collateral flow) 7,8,12,17,18 . In other words, circle collateral flow affects cICA-PO status as determined via CTA.…”
Section: Discussionmentioning
confidence: 99%
“…Pseudoocclusion of ICA on single-phase CTA has been studied before, and the authors concluded that single-phase CTA is not reliable to distinguish true occlusions from pseudoocclusions and that there are up to 15% -32.4% cases with pseudo-occlusion. The differentiation between true occlusion and pseudo-occlusion is crucial, because the planning of the endovascular intervention and treatment for acute strokes might change (17,18). We think a multiphase CTA with extended scan range on the A2 and A3 phases might be a potential solution to rule out pseudo-occlusion based on CTA findings, but further well-designed studies for this issue are required.…”
Section: Discussionmentioning
confidence: 99%
“…Carotid artery pseudo-occlusion is defined as segmental occlusion at the origin of the ICA with very thin distal flow. 8 It may be falsely diagnosed as total ICA occlusion by means of DUS, CTA or MRA. 8 Therefore, cases of segmental ICA occlusion may be misdiagnosed as CSS.…”
Section: Discussionmentioning
confidence: 99%
“… 8 It may be falsely diagnosed as total ICA occlusion by means of DUS, CTA or MRA. 8 Therefore, cases of segmental ICA occlusion may be misdiagnosed as CSS. 9 The neurological symptoms in these patients may originate from an atherosclerotic lesion or acute partial thrombosis with a tail that continues to embolise.…”
Section: Discussionmentioning
confidence: 99%